Pengaruh Work Life Balance dan Burnout terhadap Tingkat Kepuasan Kerja Karyawan Organisasi Pelayanan Kemanusiaan: Studi pada Karyawan Organisasi Pelayanan Kemanusiaan X - Martias, Diva Arum Pratami (Jurnal Ilmu Kesejahteraan Sosial, 2024)
Nothing is more important in the work lives of employees of human service organizations than job satisfaction. Job satisfaction is fundamental to employee welfare, organizational sustainability, and welfare services. The study aims to provide an overview of the influence of work life balance and burnout on the level of job satisfaction of employees of humanitarian service organizations. The study results using the Somers’D test partially proved the hypothesis that there is a positive and significant influence of work life balance on job satisfaction of 0.571 and a p-value of 0.000, stating that employees with high work life balance tend to have high job satisfaction. There is a positive and significant influence of burnout on job satisfaction of 0.635 and a p-value of 0.000, indicating that employees with high burnout tend to have high job satisfaction. It is hoped that this research can contribute to the development of information regarding the influence of work life balance and burnout on the level of job satisfaction in working in humanitarian service organizations so that it can be taken into consideration in carrying out social interventions.